MiR-103a-3p Promotes Zika Virus Replication by Targeting OTU Deubiquitinase 4 to Activate p38 Mitogen-Activated Protein Kinase Signaling Pathway - Ye, Haiyan; Kang, Lan; Yan, Xipeng; Li, Shilin; Huang, Yike; Mu, Rongrong; Duan, Xiaoqiong; Chen, Limin (Frontiers in Microbiology, 2022)
Background: MicroRNAs (miRNAs) play critical roles in regulating virus infection and replication. However, the mechanism by which miRNA regulates Zika virus (ZIKV) replication remains elusive. We aim to explore how the differentially expressed miR-103a-3p regulates ZIKV replication and to clarify the underlying molecular mechanism. Methods: Small RNA sequencing (RNA-Seq) was performed to identify differentially expressed miRNAs in A549 cells with or without ZIKV infection and some of the dysregulated miRNAs were validated by RT-qPCR. The effect of miR-103a-3p on ZIKV replication was examined by transfecting miR-103a-3p mimic or negative control into A549 cells with or without p38 MAPK inhibitor SB203580 and expression levels of ZIKV NS5 mRNA and NS1 protein were detected by RT-qPCR and Western blot, respectively. The potential target genes for miR-103a-3p were predicted by four algorithms and further validated by mutation analysis through luciferase reporter assay. The predicated target gene OTU deubiquitinase 4(OTUD4) was over-expressed by plasmid transfection or silenced by siRNA transfection into cells prior to ZIKV infection. Activation status of p38 MAPK signaling pathway was revealed by looking at the phosphorylation levels of p38 (p-p38) and HSP27(p-HSP27) by Western blot. Results: Thirty-five differentially expressed miRNAs in ZIKV-infected A549 cells were identified by RNA-Seq analysis. Five up-regulated and five down-regulated miRNAs were further validated by RT-qPCR. One of the validated up-regulated miRNAs, miR-103a-3p significantly stimulated ZIKV replication both at mRNA (NS5) and protein (NS1) levels. We found p38 MAPK signaling was activated following ZIKV infection, as demonstrated by the increased expression of the phosphorylation of p38 MAPK and HSP27. Blocking p38 MAPK signaling pathway using SB203580 inhibited ZIKV replication and attenuated the stimulating effect of miR-103a-3p on ZIKV replication. We further identified OTUD4 as a direct target gene of miR-103a-3p. MiR-103a-3p over-expression or OTUD4 silencing activated p38 MAPK signaling and enhanced ZIKV replication. In contrast, OTUD4 over-expression inhibited p38 MAPK activation and decreased ZIKV replication. In addition, OTUD4 over-expression attenuated the stimulating effect of miR-103a-3p on ZIKV replication and activation of p38 MAPK signaling. Conclusion: ZIKV infection induced the expression of miR-103a-3p, which subsequently activated p38 MAPK signaling pathway by targeting OTUD4 to facilitate ZIKV replication.